Tumour-infiltrating lymphocyte therapy landscape: prospects and challenges - Arkadiusz Z Dudek; Jeffrey Johnson; Ruqin Chen; Ali Rezazadeh (BMJ Oncology)
Tumour-infiltrating lymphocyte (TIL) therapy has emerged as a promising adoptive cell transfer strategy for solid tumours. The recent accelerated approval of lifileucel by the Food and Drug Administration marks a significant milestone in the clinical application of TIL therapy. This review comprehensively examines the historical development, biology, clinical efficacy, safety and limitations of TIL therapy. We explore advancements in TIL manufacturing, including novel culture techniques, genetic modifications and automation, to enhance scalability and effectiveness. Despite promising results, TIL therapy faces challenges such as high-dose interleukin-2 toxicity, complex manufacturing processes and immune evasion mechanisms. Emerging strategies, including checkpoint inhibitor combinations, engineered TIL constructs and metabolic reprogramming, aim to improve TIL therapeutic efficacy. This review provides insights into the evolving landscape of TIL therapy and its potential to enhance current cancer immunotherapy.